Constructing and implementing a green taxation system in China under the dual-carbon target - Liu, Hehe (Frontiers in Environmental Science, 2024)
Reducing carbon dioxide emissions and achieving carbon neutrality have become hot topics of global concern. China has elevated its response to climate change to a national strategic level, where the green tax system plays a crucial role in implementing the dual-carbon strategy. This paper systematically analyzes the green tax systems of the Organisation for Economic Co-operation and Development (OECD) -encompassing environmental pollution taxes, energy taxes, vehicle and transportation taxes, and resource taxes. Based on this analysis, it proposes that China should establish a multifaceted green tax system including environmental protection tax, resource tax, and farmland occupation tax. Furthermore, it suggests an integrated approach combining systematic tax incentives such as corporate income tax, value-added tax, consumption tax, and vehicle purchase tax. This comprehensive green taxation framework, covering development, production, consumption, and emission stages, aims to drive high-quality green economic and social development through both tax incentives and restrictions, implementing a "dual-driving" mechanism. This study provides a basic framework and practical path for building a green tax system in China, especially studying the sources of different green taxes and their interrelationships, which enriches the theoretical and practical values related to taxation.